Nutritional and Chemical Composition of the Costa Rican Guava (Psidium friedrichsthalianum [O. Berg] Nied): An Underexploited Edible Fruit with Nutritional and Industrial Potential - Muñoz Arrieta, Rodrigo (2021)
The nutritional and chemical composition of the Costa Rican guava was evaluated by proximate analysis, amino acids, sugars, organic acids, vitamins, and minerals composition. The fatty acid and proanthocyanidin (PAC) profiles were also determined. Proximate analysis showed that Costa Rican guava has a moisture content of 82.10 g/100 g, crude fat 0.91 g/100 g, protein 0.51 g/ 100 g, dietary fiber 7.10 g/100 g, and carbohydrate 8.48 g/100 g. Arginine is the predominant essential amino acid. Sucrose and citric acid are the predominant sugar and organic acid, respectively. Apart from ascorbic acid, niacin is the predominant vitamin. Sodium and calcium are the predominant minerals. Linoleic and α-linolenic acids are the predominant fatty acids. Costa Rican guava PAC contain exclusively B-type interflavan bonds with molecular masses typical of (epi)catechin monomers. To the best of our knowledge, this is the first study to provide a detailed description of the nutritional and chemical composition of the Costa Rican guava.